1978
DOI: 10.1037/0022-006x.46.1.119
|View full text |Cite
|
Sign up to set email alerts
|

Influence of contextual cues on the efficacy of desensitization and a credible placebo in alleviating public speaking anxiety.

Abstract: This investigation was designed to determine the extent to which contextual cues mediated the effectiveness of systematic desensitization and a plausible placebo in alleviating public speaking anxiety. After participating in a public speaking situation that allowed the collection of self-report, physiological, and behavioral manifestations of anxiety, 67 subjects were randomly assigned to receive five sessions of either desensitization, "T scope" therapy, or no treatment. Each of these conditions was conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1981
1981
2005
2005

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…To date, at least 11 studies have shown that credible expectancy modification procedures are capable of producing as great a reduction in fear as that produced by systematic desensitization (Gatchel, Hatch, Maynard, Turns, & Taunton-Blackwood, 1979; Kirsch & Henry, 1977; Kirsch et al, 1983; Lick, 1975; Marcia, Rubin, & Efran, 1969; McGlynn, 1971; McGlynn, Gaynor, & Puhr, 1972; McGlynn, Reynolds, & Linder, 1971; McReynolds et al, 1973; Slutsky & Allen, 1978; Tori & Worell, 1973). In addition, Gelder et al (1973) found an expectancy modification procedure to be as effective as desensitization in treating animal and tissue damage phobias.…”
Section: Expectancy and Fearmentioning
confidence: 99%
“…To date, at least 11 studies have shown that credible expectancy modification procedures are capable of producing as great a reduction in fear as that produced by systematic desensitization (Gatchel, Hatch, Maynard, Turns, & Taunton-Blackwood, 1979; Kirsch & Henry, 1977; Kirsch et al, 1983; Lick, 1975; Marcia, Rubin, & Efran, 1969; McGlynn, 1971; McGlynn, Gaynor, & Puhr, 1972; McGlynn, Reynolds, & Linder, 1971; McReynolds et al, 1973; Slutsky & Allen, 1978; Tori & Worell, 1973). In addition, Gelder et al (1973) found an expectancy modification procedure to be as effective as desensitization in treating animal and tissue damage phobias.…”
Section: Expectancy and Fearmentioning
confidence: 99%
“…McGlynn, Kinjo, and Doherty (1978) showed that an elaborate and credible placebo treatment is just as effective as relaxation therapy, as measured by questionnaires, in students suffering from examination fears. Further, Slutsky and Allen (1978) showed that as long as the treatment is seen as therapeutic (as opposed to investigatory) a placebo treatment is as effective as SD. Thus, it remains to be seen if the STR handout has enough intrinsic merit to surpass a "hard-sell" inert procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond Kirsch’s summary, the complete findings reported by Slutsky and Allen (1978) also showed the superiority of systematic desensitization on physiological variables, the robustness of systematic desensitization independent of situational factors, and greater incidence of deterioration for the credible control procedure than for systematic desensitization. The original investigators interpreted these results as support for counterconditioning, rather than expectancy.…”
Section: Selective and Incomplete Informationmentioning
confidence: 94%
“…Expectancy modification represents an intent or a presumption about the effects of a control procedure on expectancies; however, unless the intended expectancies are validated, the label expectancy modification procedure denotes only a set of operations, not the explanatory mechanism that the label connotes. Of the 15 experiments cited by Kirsch (p. 1193) as employing expectancy modification procedures, 8 did not validate that expectancies had been instilled or modified, nor did the original authors use the label, “expectancy modification procedure.” In three other cited experiments, rather than measuring response expectancy prior to or during treatment, procedural authenticity or credibility was measured only at posttesting (McReynolds, Barnes, Brooks, & Rehagen, 1973; Slutsky & Allen, 1978; Tori & Worell, 1973). The timing and content of these assessments preclude causal attributions to response expectancies.…”
Section: Measurement and Validationmentioning
confidence: 99%